LOCAL WISDOM AND CULTURAL VALUES IN AL-AZHAR TAFSIR - Husnel Anwar; Mhd. Roihan Nasution; Muhammad Doli Zamzami Siregar (Studia Sosia Religia, 2020)
Abstract The problem of this research is how can the local cultural values in Al-Azhar Tafsir. The purpose of this research is knowing local culture values in Al-Azhar Tafsir and analyzing the purpose of HAMKA putting local cultural values ini Al-Azhar Tafsir. The method of this research is library research and uses a study approach of character studies andcontent analytics. Researchers found that HAMKA's attitude was divided into two in linking local cultural values in Al Azhar's Tafsir. First, wanting to preserve local cultural values such as Aphorism, Verse, Poetry, Parable, Pameo and others. The second, strongly opposed and warned people of traditions that were contrary to Islamic Shari'a such as "adorig sea", giving offerings and others. And among the main objectives of HAMKA to include local cultural values was to approach Islamic da'wah to Indonesian people through local cultural values in its interpretation. And also introduce to the world of readers about Malay identity and Local Wisdom. And it also contained an invitation to noble morals as Religion and Culture motivate it and there were also politic and ethical politic invitations because at the time of writing this interpretation, the Indonesian political atmosphere was currently unstable. Therefore, it is very good to make Al Azhar's Tafsir become one of the references in preaching Islam on this Malay Earth and hopefully in the future there will be a Ilmiyah Figure and Study that combines Islamic Sharia and Local Cultural Values in a fair and balanced way. Keywords: Local Wisdom, Values and Al-Azhar Tafsir